IMPLEMENTATION OF THE TOGETHER LEARNING MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES ON THE CONCEPT OF MOLECULAR GEOMETRY - Rusman Rusman; Reza Resita Vonna; Ratu Fazlia Inda Rahmayani (FKIP USK, 2020)
The purpose of this study was to analyze student learning outcomes, describe student activities and describe student responses after the application of the learning together model on the material of molecular form at SMA Negeri 1 Krueng Barona Jaya. This is a descriptive study with a qualitative approach. The population in this study were students of class X SMA Negeri 1 Krueng Barona Jaya. Data were collected by observing student activities, learning outcomes tests and filling out student response questionnaires. The results of the percentage of student activity from the first meeting to the third meeting in a row, namely 71%, 84% and 85% showed that the activity of students increased significantly. The percentages of learning outcomes at the first to third meetings were 67.50%, 77.50% and 87.50% which showed an increase and classical mastery achievement. Students showed a positive response to the application of the learning together model on the material in the form of molecules with a percentage of 94.07%. The learning together model can improve students' activities and learning outcomes. Students are enthusiastic in participating in learning using the learning together model and most of them give a positive response.